Growth and yield performance of kale (Brassica oleracea L. var. acephala) in organic-based soilless substrates under greenhouse conditions - Marissa, P B (Plant Science Today, 2026)
Soil degradation and limited arable land continue to constrain vegetable production in upland areas of the Philippines. This study evaluated the growth and yield performance of kale (Brassica oleracea L. var. acephala) grown in organic-based soilless substrates under greenhouse conditions. A Completely Randomized Design (CRD) was employed with 5 treatments replicated three times. The treatments consisted of combinations of Processed Chicken Manure (PCM), Carbonized Rice Hull (CRH) and various organic additives, including Vermicompost (VC), Coconut Coir Dust (CCD), Spent Mushroom Compost (SMC) and a control (garden soil + river sand). Growth parameters measured included plant height (PH), root length (RL) and root weight (RW), while yield components comprised leaf length (LL), leaf number (LN), economic yield (EY), biological yield (BY) and harvest index (HI). Results showed that Treatment 1 (PCM + CRH + VC) and Treatment 3 (PCM + CRH + SMC) produced the tallest plants, longest leaves and highest yields. Treatment 2 (PCM + CRH + CCD) promoted superior root development, whereas the control (T₅) recorded the lowest performance in both growth and yield attributes. Organic-based soilless substrates, particularly those enriched with VC or SMC, significantly enhance kale growth and productivity under controlled conditions. The use of these sustainable substrate formulations offers a viable approach to improving vegetable production in land-constrained and ecologically fragile upland environments, supporting the goals of sustainable and climate-resilient agriculture.